2007
DOI: 10.1002/chem.200701014
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Gold and Silver Nanoparticles by Using Redox‐Active Amphiphiles and Their Phase Transfer to Organic Solvents

Abstract: An in situ reduction approach to synthesizing gold and silver nanoparticles by using a series of newly designed, redox-active amphiphiles at basic pH is described. These amphiphiles are the conjugates of a fatty acid (e.g., oleic acid, stearic acid, and lauric acid) and a redox-active amino acid (e.g., tryptophan or tyrosine). The amphiphile-coated nanoparticles are then efficiently transferred from water to different nonpolar organic media (such as benzene, toluene, xylene, cyclohexane, and hexane) simply by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 63 publications
5
49
0
Order By: Relevance
“…[50][51][52][53] This encouraged us to explore the in situ reduction technique further to synthesize MNPs using newly designed redox-active ILs as reducing/stabilizing agents. It is known that ascorbic acid generally exhibits keto-enol tautomerisim, the enol form of which is susceptible to ionization in aqueous solution and has been used as a versatile reducing agent for variety of metal ion precursors to prepare MNPs.…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52][53] This encouraged us to explore the in situ reduction technique further to synthesize MNPs using newly designed redox-active ILs as reducing/stabilizing agents. It is known that ascorbic acid generally exhibits keto-enol tautomerisim, the enol form of which is susceptible to ionization in aqueous solution and has been used as a versatile reducing agent for variety of metal ion precursors to prepare MNPs.…”
Section: Introductionmentioning
confidence: 99%
“…This showed that the quantity of CdTe QDs in the blending system affected the average particle size of CdTe QDs significantly. Considering all the phenomena above, THF can be inferred as the main factor caused the particle size variation of CdTe QDs 27 . When THF added in the system, no matter C-CPA was added or not added in the system, the particle size of CdTe QDs all changed and as the ratio of THF increasing, the affect increased as well.…”
Section: Resultsmentioning
confidence: 99%
“…[14] We demonstrate that this hybrid system exhibits an unambiguous optical fingerprint of the doubly charged silver cluster (Ag 4 2+ ) stabilized by a salt-bridge (SB) interaction with the organic moiety. Thus, we propose the use of its optical signature as a marker to monitor early stages of seeding processes for particle growth.…”
Section: +mentioning
confidence: 99%